Presence of benznidazole conjugated metabolites in urine identified by β-glucuronidase treatment - Marson, María Elena (2020)
Chagas disease is a serious public health problem in Latin America and, due to migration, in other nonendemic regions. Benznidazole (BNZ) is first choice drug in pediatric therapeutics. However, little is known regarding its metabolism in humans. The aim of the study was to isolate and identify products of human BZN metabolism in urine samples obtained from a pediatric Chagas patient and a healthy adult volunteer both treated with BZN. Urine samples were collected after dose of BNZ. Urine was treated with β-glucuronidase followed by an extraction procedure under two different pH conditions and a HPLC/UV and MS/MS identification of BZN and its metabolites. BZN (m/z 260.09847) was identified in all urine extracts. Peaks from each extracted chromatograms were selected for MS and MS/MS identification. Three compounds structurally related to BZN were identified: BZN-Na+ (m/z 283.08009), N-amine-BZN (m/z 230.12307) and N-hydroxi-amine-BZN (m/z 246.11702). BNZ-Na+ was identified in all extracts, but N-amine-BZN and N-hydroxi-amine-BZN were only observed in those extracts treated with β-glucuronidase. This is the first experimental report showing elimination of BZN N-reduced metabolites in urine. As they were released after treatment with β-glucuronidase it can be suggested that glucuronization plays a role in BNZ metabolism and renal elimination.